ANALISIS STRUKTUR PENDAPATAN DAN PENGELUARAN KONSUMSI RUMAH TANGGA PETANI NENAS DI DESA KUALU NENAS KECAMATAN TAMBANG KABUPATEN KAMPAR - Bayu Kurniawan; Novia Dewi; Roza Yulida (Indonesian Journal of Agricultural Economics, 2017)
The purposes of this research were 1) assessing the income structure of pineapple farmer household in Kualu Nenas, Tambang, Kampar, analyzing the consumption expenditure of pineapple farmer household in Kualu Nenas Village Tambang Kampar, 3) analyzing the dominant factors that influence food consumption expenditure of pineapple farmer household conducted in the Kualu Nenas Village Tambang District Kampar Regency by using survey method. The respondents were chosen by using simple random sampling technique. The population of this research were pineapple farmers with the total number was 67 farmers which was selected randomly of 30 farmers. The data was analyzed by using income analysis, income structure analysis and binary logistics analysis. Based on the result of the income structure analysis, the biggest household income is from the pineapple farm. The consumption system of pineapple farmer household shows that the expenditure of food comsumption is more than non food comsumption. The dominant factor that influences the system of the pineapple farmer household food comsumption is job status. The correlation between job status and opportunities expenditure allocation is inversed. It means that the use of more laborer from outside of the family causing the farmers' opportunity in allocating the consumption expenditure became smaller.